2019
DOI: 10.3390/ijerph16132435
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Review: The (Mental) Health Consequences of the Northern Iraq Offensive of ISIS in 2014 for Female Yezidis

Abstract: The Yezidis who represent a religious minority living in Northern Iraq were particularly affected by the persecution by ISIS (Islamic state of Iraq and Syria, syn.: ISIL—Islamic state of Iraq and the Levant) that gained power after 2013. This paper gives an overview of the events and the mental health consequences on the Yezidi community as well as associated influences on affected female Yezidis. Based on a systematic literature search, the aspects of “Persecution by ISIS and actual situation of the Yezidi co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Most relevant has been reports from organisations assisting in the rehabilitation of Yazidi females, which have indicated that these women are at increased risk of suicide attempts and completions but more rigorous investigations are needed [ 27 ]. In the past 4 years, efforts by the Yezidi community to undertake healing rituals in their holy city Lalish to assist in the rehabilitation of formerly enslaved females, is likely to have a positive impact on these tragic outcomes, but the distinct possibility of ongoing discrimination perpetrated within their own community continues to play a role their suicide behaviours [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most relevant has been reports from organisations assisting in the rehabilitation of Yazidi females, which have indicated that these women are at increased risk of suicide attempts and completions but more rigorous investigations are needed [ 27 ]. In the past 4 years, efforts by the Yezidi community to undertake healing rituals in their holy city Lalish to assist in the rehabilitation of formerly enslaved females, is likely to have a positive impact on these tragic outcomes, but the distinct possibility of ongoing discrimination perpetrated within their own community continues to play a role their suicide behaviours [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another report, survivors described girls as young as nine to be "married" to militants [11]. ISIS developed an organized system of kidnapping, transportation, and accommodations of enslaved Yazidi women including a register and an online auction site [29]. While ISIS is not the first terrorist group to use kidnapping and sex slavery as a terrorist tool, the scale and extent at which slavery and sexual violence is incorporated into the social and financial fabric of the organization is unprecedented [30].…”
Section: Terrorism and Islamic State Of Iraq And Syria (Isis)mentioning
confidence: 99%
“…The consequences of war and genocide had poor impact on the mental health and may persist for long life (Al Shawi et al, 2019; Akhavan et al, 2020; Jäger et al, 2019). The current study sought to examine the traumatic events and PTSD among Yazidi population after ISIS invasion, and it was carried out 4 years after the conflict in 2014 (a post conflict study), therefore the study might measure long term effect of trauma exposure on mental health of Yazidi population.…”
Section: Discussionmentioning
confidence: 99%
“…They suffered from extreme psychosocial distress as a result of the serious violence, the loss or captivity of family members, ongoing displacement with many suicidal attempts and other self-destructive behaviors that occurred among the displaced population which observed by UNHCR’s protection partners operating in camps in Duhok Governorate (Akhavan et al, 2020; Jäger et al, 2019; United Nations High Commissioner for Refugees, 2019).…”
Section: Introductionmentioning
confidence: 99%